2018
DOI: 10.2196/jmir.8090
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Interventions Delivering Home-based Support Group Videoconferencing: Systematic Review

Abstract: BackgroundGroup therapy and education and support sessions are used within health care across a range of disciplines such as chronic disease self-management and psychotherapy interventions. However, there are barriers that constrain group attendance, such as mobility, time, and distance. Using videoconferencing may overcome known barriers and improve the accessibility of group-based interventions.ObjectiveThe aim of this study was to review the literature to determine the feasibility, acceptability, effectiven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
184
3
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(233 citation statements)
references
References 75 publications
19
184
3
5
Order By: Relevance
“…Technical training before MBSR intervention and access to support during the intervention was considered necessary. This is in accordance with Banbury et al (32) who found that this is central to the acceptability of home-based VC in groups. It might also be of particular relevance to participants who, due to CP, have sensory, motor, cognitive, or other challenges that result in a need for individual adaptations.…”
Section: Feasibility and Acceptability Of Group-and Vc-based Mbsrsupporting
confidence: 92%
See 1 more Smart Citation
“…Technical training before MBSR intervention and access to support during the intervention was considered necessary. This is in accordance with Banbury et al (32) who found that this is central to the acceptability of home-based VC in groups. It might also be of particular relevance to participants who, due to CP, have sensory, motor, cognitive, or other challenges that result in a need for individual adaptations.…”
Section: Feasibility and Acceptability Of Group-and Vc-based Mbsrsupporting
confidence: 92%
“…In the first data set (experience of outcome of intervention), we generated initial codes for the semantic meaning in the text, secondly reviewed and refined themes in the form of text extracts of each theme, and then defined and named the themes. In the second data set (experience and evaluation of the use of VC) we based the thematic analysis on the themes in Banbury's research (32), highlighting aspects of feasibility and acceptability, such as usability, communication adaption, and accessibility. Since the data from the focus group interviews were a deepening of the written comments in the evaluation questionnaire, these data are reported together.…”
Section: Resultsmentioning
confidence: 99%
“…Internationally, video is used for conducting consultations in the routine delivery of health care, with use reported across a range of settings and clinical specialties, including specialist diabetes care, 1 paediatric acute care, 2 specialist palliative care services, 3 primary care, 4 clinical oncology, 5 and mental health settings. 6 Despite offering advantages relating to its remoteness and convenience for patients, 7,8 adoption and uptake have been slow in healthcare settings. 9,10 This has particularly been the case for primary care settings, where levels of use are low.…”
Section: Introductionmentioning
confidence: 99%
“…Attending face‐to‐face group meetings may present challenges to specific cancer populations as they navigate health care appointments while maintaining employment and child care responsibilities, in those who are hesitant to attend structured groups in institutional settings, or in patients who must be isolated for infection control after procedures such as chemotherapy and HSCT. Technological innovations now make it possible to offer interventions at home over a broadband platform . In RCTs, online programs that allow patients with breast cancer to create personal blog sites improved mood .…”
Section: Sm and The Immune Processes In Patients With Cancermentioning
confidence: 99%
“…Technological innovations now make it possible to offer interventions at home over a broadband platform. 129 In RCTs, online programs that allow patients with breast cancer to create personal blog sites improved mood. 130 Although these venues provide support resources, less is known about the value of remotely delivered, empirically validated SM interventions that affect stress and immune parameters (eg, CBSM), although RCTs are underway examining their impact in patients with breast cancer.…”
Section: Remotely Delivered Sm Interventionsmentioning
confidence: 99%